Living with fire & water - Gannon, Ben, author; Kampf, Stephanie, author; Wilson, Codie, author; Jones, Kelly, author; Wei, Yu, author; MacDonald, Lee, author; Mattor, Katherine, author; Nelson, Peter, author; Cheng, Tony, author; Wolk, Brett, author; Colorado Water, publisher (Colorado State University. Libraries, 2018)
Wildfire is considered a critical risk to community drinking water supplies in the western U.S. Our team integrates research from the physical and social sciences to better characterize wildfire risk to water supplies and to evaluate the effects of pre- and post-fire risk mitigation approaches.
Keywords: Water-supply -- Effect of fires on; Drinking water -- Effect of fires on; Water-supply -- West (U.S.); Hazard mitigation -- Economic aspects; Hazard mitigation -- Social aspects; Post-fire forest management